An Efficient Parametric Modeling, Evaluation and Optimization Strategy for Aerodynamic Configuration Design of eVTOL Aircraft - Yiming Du; Zehao Liu; Meizhu Shen; Jiang Wu; Kexin Zhang; Chuanye Jiang; Jiale Zhong (Aerospace Research Communications)
Traditional aerodynamic design faces significant limitations in modeling and computational efficiency during conceptual design stage. A phased collaborative aerodynamic design strategy for eVTOL aircraft was established, by combining the OpenVSP platform for rapid parametric modeling and evaluation, a Kriging surrogate framework with an improved differential evolution algorithm for optimization, and the SUAVE platform for propeller reverse design. In the wing-body (WB) optimization phase, 23 configuration parameters such as the wing shape and location were adjusted. The aerodynamic evaluation was conducted using the Vortex Lattice Method (VLM) in OpenVSP, resulting in a 9.3% increase in the lift-to-drag ratio (L/D). During the wing-body-propeller (WBP) coupling optimization phase, the Actuator Disk Theory (ADT) was incorporated into WB model to quantify the slipstream effects. After optimizing the key geometric parameters such as disk diameter and location, the comprehensive propulsion efficiency and lift-to-drag ratio (η·/L/D) was increased by 14%. Relative performance parameters were then transferred to SUAVE to reconstruct the propeller based on the Betz-BEM theory. The RANS high-fidelity verification of the optimized WBP model shows high consistency in the trends of lift coefficient Cl and L/D calculated by VLM, with the propeller thrust error 5.2%, and the Cl error 9.7%, which confirms the engineering reliability and efficiency of the proposed strategy.